Treatment of the textile wastewater through fungi:: a sustainable alternative - Chicatto, Juliane Andressa; Gonçalves, Marcel Jefferson; Altmajer-Vaz, Deisi; Tavares, Lorena Benathar Ballod (Sustainability in Debate, 2018)
The decolorization of textile effluents represents a considerable challenge because it contains certain degradation resistant compounds, such us dyes. Chemical, physical and biological methods are used for the removal of dyes from wastewater; however, conventional treatments of these effluents do not appear effective in removing dyes compounds. It actually has several drawbacks such as the high cost of the chemicals used, the generation of hazardous secondary wastes or its disposal problem and limited applicability. A fungal culture has the capability to acclimate its metabolism to changing environmental conditions. This ability is vital for their existence. Here, intra and extracellular enzymes help in metabolic activity. These enzymes have the capacity to degrade various dyes present in the textile wastewater. Due to these enzymes, fungal cultures seem to be suitable for the degradation of dyes in textile wastewater. For these reasons, the purpose of this interdisciplinary approach review is to provide innovative solutions to environmental problems, particularly to improve the treatment of industrial textile effluents with the use of biomass generated in the agroindustry, like palm tree extraction.